Numerical model for predicting the structural response of composite UHPC–concrete members considering the bond strength at the interface. (1st May 2019) - Yin, Hor; Shirai, Kazutaka; Teo, Wee
Abstract: In this study, an improved finite element (FE) model was developed for the prediction of the structural behaviour of reinforced concrete members strengthened with ultrahigh-performance concrete (UHPC). A concrete damage model and an implicit solver in LS-DYNA were adopted in the numerical simulation. The model was calibrated and validated using experimental data. Accurately representing the interfacial bond characteristics of composite UHPC–concrete members was the primary challenge in developing the modelling technique. A novel technique using equivalent beam elements at the interface between UHPC and normal strength concrete (NSC) substrate was proposed for this purpose. The material properties of the equivalent beam elements were defined to represent the equivalent bond characteristics of NSC. The developed FE model was found to be able to effectively and efficiently predict the structural response of composite UHPC–concrete members with good accuracy.